Investigating the effect of freezing method, voltage gradient, and probe type on quality characteristics of Turkey meat during the ohmic thawing process - Shabnam Safari; Mohsen Zandi; Ali Ganjloo (Heliyon)
This research addresses the gap in efficient thawing methods by investigating the effects of ohmic thawing variables and freezing methods on the thawing speed and quality attributes of ground turkey breast, aiming to identify the optimal ohmic thawing method and compare it with traditional air and water thawing techniques. The variables for ohmic thawing consisted of voltage gradient (10, 15, and 20 V/cm), freezing method (Snap (rapid freezing of samples in liquid nitrogen at −210 °C), −70, and −20 °C), and probe type. The results showed that the snap-freezing method demonstrated superior functional and quality characteristics. The optimized ohmic thawing method, using snap freezing at 15 V/cm, improves thawing efficiency, cutting thawing time by up to 78.8 % compared to traditional methods. It also reduces thawing loss by up to 45 % and minimizes evaporation loss, preserving protein solubility and decreasing lipid oxidation (TBARS reduction of up to 50 %). The thawing rate of the optimal ohmic thawing method was 2.3 times faster than the air thawing method and 4.9 times faster than the water thawing method. The method of ohmic thawing significantly reduced all losses and had a significant impact on decreasing the solubility of protein and TBARS while also maintaining the pH stability of the sample (p˂0.05). The ohmic thawing preserved the sample's color and positively affected the color variables (L∗, b∗, ΔE, ΔC, hue angle, and chroma).